2014
DOI: 10.1016/j.febslet.2014.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin ligase Cbl‐b acts as a negative regulator in discoidin domain receptor 2 signaling via modulation of its stability

Abstract: a b s t r a c tDiscoidin domain receptor 2 (DDR2), a collagen receptor tyrosine kinase, initiates signal transduction upon collagen binding, but little is known as to how DDR2 signaling is negatively regulated. Herein we demonstrate that Cbl family member Cbl-b predominantly promotes the ubiquitination of DDR2 upon collagen II stimulation. Cbl-b-mediated ubiquitination accelerates the degradation of activated DDR2. Finally, the production of MMP-13, a downstream target of DDR2, is enhanced in Cbl-b-knocked dow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Cbl protein-mediated ubiquitination can target activated RTK for degradation, either by facilitating endocytic sorting into lysosomes or by promoting proteasomal degradation (38). In a previous study, Cbl-b was experimentally shown to function as a negative regulator in the DDR2 by promoting the ubiquitination and degradation of DDR2 (22). All three members of the Cbl family of proteins share a highly homologous N-terminal tyrosine kinase binding region, which serves as the structural platform for binding to phospho-tyrosine residues (39).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cbl protein-mediated ubiquitination can target activated RTK for degradation, either by facilitating endocytic sorting into lysosomes or by promoting proteasomal degradation (38). In a previous study, Cbl-b was experimentally shown to function as a negative regulator in the DDR2 by promoting the ubiquitination and degradation of DDR2 (22). All three members of the Cbl family of proteins share a highly homologous N-terminal tyrosine kinase binding region, which serves as the structural platform for binding to phospho-tyrosine residues (39).…”
Section: Discussionmentioning
confidence: 99%
“…As previously reported, Cbl-b, a family of E3 ubiquitin ligases, interacts with DDR2 and promotes its ubiquitination, resulting in its degradation (22). We next examined the interaction of DDR2 with Cbl-b using immunoprecipitation.…”
Section: Ddr2 Protein Harboring the E655k Mutation Is Sensitive To Thmentioning
confidence: 96%
“…Moreover, metalloproteinases are enzymes that mediate photoaging and tissue remodeling 46 . Some metalloproteinases like MMP13 are negatively regulated by Cbl-b 47 . UVB-irradiated Cbl-b −/− mice had an increase of MMP12 expression in cells of the epidermis (Fig.…”
Section: Discussionmentioning
confidence: 99%